Protective Effect of Lemon Essential Oil and Its Major Active Component, D-Limonene, on Intestinal Injury and Inflammation of E. coli-Challenged Mice - Zhao, Chen; Zhang, Zhuo; Nie, Dechao; Li, Yanling (Frontiers in Nutrition, 2022)
The inflammation caused bacterial infection threats public health worldwide. The natural plant essential oils have the effective activity of anti-inflammation. Herein, we investigate the anti-inflammation effects and mechanisms of lemon essential oil (LEO) and its main activated component d-limonene. Relevant antioxidant indexes include superoxide dismutase (SOD), malondialdehyde (MDA), and myeloperoxidase (MPO). Relevant Inflammatory indexes include interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor alpha (TNF-α). Relevant tight junction protein indicators include zona occludens 1 protein (ZO-1), occludin and claudin. We found that LEO (300 mg/kg) and d-limonene (600 mg/kg) have the antioxidant and anti-inflammation activity on the infected mice by reducing the contents of MDA, MPO and inflammatory factors of TNF-α, IL-1β and IL-6, while increasing the contents of SOD, respectively. H&E staining of duodenum showed that lEO and d-limonene could reduce inflammatory cell infiltration and maintain the orderly arrangement of epithelial cells. Moreover, LEO (600 mg/kg) and d-limonene (300 mg/kg) alleviated intestinal barrier injury by increasing the relative expression of ZO-1, occludin and claudin mRNA in mice duodenum. Taken it together, our results showed that the pre-treatment with LEO and d-limonene, had significantly protection of intestinal tissue and inflammation in Escherichia coli (E. coli) infected mice by increasing antioxidant indexes, decreasing serum cytokine contents and upregulating gene expressions of tight junction. Our work will shed light on the discovery of the anti-inflammatory drugs from LEO.